Overexpression of three TaEXPA1 homoeologous genes with distinct expression divergence in hexaploid wheat exhibit functional retention in Arabidopsis. - Zhaorong Hu; Na Song; Jiewen Xing; Yanhong Chen; Zongfu Han; Yingyin Yao; Huiru Peng; Zhongfu Ni; Qixin Sun (PLoS ONE, 2013)
Common wheat is a hexaploid species with most of the genes present as triplicate homoeologs. Expression divergences of homoeologs are frequently observed in wheat as well as in other polyploid plants. However, little is known about functional variances among homologous genes arising from polyploidy. Expansins play diverse roles in plant developmental processes related to the action of cell wall loosening. Expression of the three TaEXPA1 homoeologs varied dynamically at different stages and organs, and epigenetic modifications contribute to the expression divergence of three TaEXPA1 homoeologs during wheat development. Nevertheless, their functions remain to be clarified. We found that over expression of TaEXPA1-A, -B and -D produced similar morphological changes in transgenic Arabidopsis plants, including increased germination and growth rate during seedling and adult stages, indicating that the proteins encoded by these three wheat TaEXPA1 homoeologs have similar (or conserved) functions in Arabidopsis. Collectively, our present study provided an example of a set of homoeologous genes expression divergence in different developmental stages and organs in hexaploid wheat but functional retention in transgenic Arabidopsis plants.